The Effects of Strainer Types on Flow Characteristics of Anti-Drift - Bahadır Sayıncı; Mazhar Kara (Journal of Agricultural Sciences)
This study investigated the effects of four different strainer types on flow characteristics (orifice coefficient (k), exponent coefficient (n), individual flow rate deviation (φ) and discharge coefficient (Cd)) of different nozzle types. The volumetric flow rates of anti-drift (AD) and multi-range (LU) flat-fan nozzles of three different orifice sizes were determined at different operational pressures (1.5, 3.0, 4.0, 6.0 and 8.0 bars). In each treatment, the nozzles were used together with cup screen strainer of 50-mesh, slotted strainer, cylindrical strainers of 40-, 50-, and 80-meshes, and ball-check strainers of 50- and 80-meshes. The flow rate measurements were also obtained without strainers. The relation between the flow rate (Q) and spray pressure (P) for each nozzle combination (nozzle type, strainer type, and orifice size) was presented using the power regression model . The “k” coefficient, which is the slope of the line referring to the relation between the nozzle flow rate and spray pressure, was evaluated as a comparison parameter between the nozzle combinations. The “k” mean values of the nozzle types using with ball-check strainers were lower than those of the without strainer, cup screen, slotted and cylindrical strainers. This result showed that the volumetric flow rate decreased with respect to the other nozzle combinations operated at the same operational pressure. Thus, the deviation rate from the nominal flow rate of the nozzles used with the ball-check strainers exceeded the acceptable deviation limit of ±10%. As the “n” coefficients of the LU and AD nozzles used with cup screen, slotted, cylindrical strainers and without strainers were close to 0.50, the ball-check strainers resulted in increasing the “n” coefficient of the nozzles. The “n” coefficient of the nozzles used with the ball-check strainers of 50- and 80- meshes was determined as 0.586 and 0.608 for the AD nozzle, respectively and, 0.576 and 0.584 for the LU nozzle, respectively. The ball-check strainers dramatically decreased the discharge coefficient (Cd) of the nozzles compared to the other strainers and the usage without strainer. For the cup screen, slotted, cylindrical strainers and the usage without strainer, the Cd means ranged from 0.67 to 0.77 for the AD nozzle, and 0.91 to 0.94 for the LU nozzle. The Cd means of the nozzles used with the ball-check strainers of 50- and 80- meshes were determined as 0.39 and 0.34 for the AD nozzle, respectively, and 0.56 and 0.53 for the LU nozzle, respectively.